2011
DOI: 10.1097/hjh.0b013e3283455ca5
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized study comparing the antihypertensive effect of eplerenone and spironolactone in patients with hypertension and evidence of primary aldosteronism

Abstract: The antihypertensive effect of spironolactone was significantly greater than that of eplerenone in hypertension associated with primary aldosteronism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(130 citation statements)
references
References 35 publications
4
117
1
8
Order By: Relevance
“…However, one noticeable difference was the lower serum potassium level compared with the other treatment groups. In a recent study, hyperkalemia occurred more often in spironolactone than in eplerenone-treated patients (42). Therefore, we believe that the eplerenone doses used in our study might still be too low to effectively block the MR.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, one noticeable difference was the lower serum potassium level compared with the other treatment groups. In a recent study, hyperkalemia occurred more often in spironolactone than in eplerenone-treated patients (42). Therefore, we believe that the eplerenone doses used in our study might still be too low to effectively block the MR.…”
Section: Discussionmentioning
confidence: 71%
“…Considering previous studies, we are the first to investigate renal outcome depending on different therapeutic regimens in PA patients. Eplerenone is described to be as effective as spironolactone in reducing blood pressure in patients with BHA (41), whereas other studies claimed that the antihypertensive effect of spironolactone is significantly greater than that of eplerenone in PA patients (42). In the latter study, it was suggested that higher doses of eplerenone are needed to achieve the same effect as spironolactone.…”
Section: Discussionmentioning
confidence: 96%
“…Parthasarathy et al [21] reported that the antihypertensive effects of spironolactone (from 75 to 225 mg) were significantly greater than those of eplerenone (from 100 to 300 mg) in 141 patients with PA including APAs. Two studies reported the adverse events associated with spironolactone treatment, which included gynecomastia, breast pain in females and impotence.…”
Section: Discussionmentioning
confidence: 99%
“…68 However, double the dose is required to achieve an efficacy similar to that of spironolactone for lowering BP, and the ceiling effect appears to occur sooner: a 10 mmHg decreased in systolic BP at most, versus 25 mmHg for spironolactone. 69 Moreover, eplerenone must be administered twice daily to ensure activity throughout the day and is currently more expensive than spironolactone.…”
Section: Drug-based Treatment For Pamentioning
confidence: 99%